Recent Advances on PKM2 Inhibitors and Activators in Cancer Applications - Chen, Peng; Lou, Liang; Sharma, Bigyan; Li, Mengchu; Xie, Chengliang; Yang, Fen; Wu, Yihang; Xiao, Qicai; Gao, Liqian (Current Medicinal Chemistry, 2024)
Metabolic reprogramming of cells, from the normal mode of glucose metabolism named glycolysis, is a pivotal characteristic of impending cancerous cells. Pyruvate kinase M2 (PKM2), an important enzyme that catalyzes the final rate-limiting stage during glycolysis, is highly expressed in numerous types of tumors and aids in development of favorable conditions for the survival of tumor cells. Increasing evidence has suggested that PKM2 is one of promising targets for innovative drug discovery, especially for the developments of antitumor therapeutics. Herein, we systematically summarize the recent advancement on PKM2 modulators including inhibitors and activators in cancer applications. We also discussed the classifications of pyruvate kinases in mammals and the biological functions of PKM2 in this review. We do hope that this review would provide a comprehensive understanding of the current research on PKM2 modulators, which may benefit the development of more potent PKM2-related drug candidates to treat PKM2-associated diseases including cancers in future.
Keywords: activators